ANALISIS AKSES MASYARAKAT DKI JAKARTA TERHADAP AIR BERSIH PASCA PRIVATISASI AIR TAHUN 2009-2014 - Marsya Nivita Ardelia; Priyatno Harsasto; Nunik Retno (Journal of Politic and Government Studies, 2015)
Clean water is one of the human basic needs and Nation should fulfill theircitizen basic needs. DKI Jakarta Province, as Capital City of Indonesia, encounterclean water crisis which made the citizen have been hard to getting access to cleanwater. Therefore, the government proposed cooperation with private partners toimprove DKI Jakarta citizen access to clean water through Water PrivatizationPolicy. For that, the authors conducted research to discover the success of WaterPrivatization Policy in order to improve DKI Jakarta Citizen access to clean waterafter privatization of water.The approach used in this research is descriptive qualitative withinterviews data collection methods and document study. Subject were PublicWater Company in DKI Jakarta (PAM JAYA).The result showed that Water Privatization Policy in DKI Jakarta Provincewas failed because after the matter in cooperation with the private partners, thecitizen access to clean water decreases. It is caused by the performance of privatepartners that are not optimal in serving the needs of clean water citizen of DKIJakarta Province.So the authors conclude the need for this research as an evaluation ofGovernment of DKI Jakarta Province for more leverage in providing water serviceto the citizen of DKI Jakarta Province.